2000
DOI: 10.1021/bi992092e
|View full text |Cite
|
Sign up to set email alerts
|

Azotobacter vinelandii Nitrogenases Containing Altered MoFe Proteins with Substitutions in the FeMo-Cofactor Environment: Effects on the Catalyzed Reduction of Acetylene and Ethylene

Abstract: Altered MoFe proteins of Azotobacter vinelandii Mo-nitrogenase, with amino acid substitutions in the FeMo-cofactor environment, were used to probe interactions among C(2)H(2), C(2)H(4), CO, and H(2). The altered MoFe proteins used were the alpha-195(Asn) or alpha-195(Gln) MoFe proteins, which have either asparagine or glutamine substituting for alpha-histidine-195, and the alpha-191(Lys) MoFe protein, which has lysine substituting for alpha-glutamine-191. On the basis of K(m) determinations, C(2)H(2) was a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
94
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 46 publications
12
94
0
Order By: Relevance
“…7. We have studied the effects of substitutions at these two positions on nitrogenase function in some detail previously [14,26,27,[32][33][34]43,44]. This information led us to chose the aH195Q, aH195N and aQ191K MoFe proteins as suitable vehicles to assist in determining the potential function(s) of the three-electron-reduced FeMo-cofactor-based species responsible for the new S = 3/2 signal that we call signal 1b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7. We have studied the effects of substitutions at these two positions on nitrogenase function in some detail previously [14,26,27,[32][33][34]43,44]. This information led us to chose the aH195Q, aH195N and aQ191K MoFe proteins as suitable vehicles to assist in determining the potential function(s) of the three-electron-reduced FeMo-cofactor-based species responsible for the new S = 3/2 signal that we call signal 1b.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of wild-type (a-191 Gln /a-195 His ), DJ255 (a-191 Lys /a-195 His ), DJ178 (a-191 Gln /a-195 Asn ), and DJ540 (a-191 Gln /a-195 Gln ) strains of A. vinelandii, nitrogenase derepression, cell-extract preparation, purification of the nitrogenase MoFe protein component, and exchange into 25 mM HEPES (pH 7.4) were performed as previously described [32][33][34]. The resulting MoFe protein specific activities were 2600 (wild-type), 1500 (aQ191K), 1500 (aH195N), and 2700 (aH195Q) nmol H 2 (min mg MoFe protein) À1 , under 101 kPa Ar in the presence of a 20-fold molar excess of wild-type Fe protein with an ATP/2e À value of 5.1 ± 0.5.…”
Section: Cell Growth and Protein Purificationmentioning
confidence: 99%
“…These are of particular interest as they bind, but do not reduce N 2 well or at all respectively. and it has been suggested that the α-H195 residue plays a role in channelling protons to the FeMo-cofactor active site [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work on wild-type nitrogenase revealed that proton addition to acetylene during its reduction to ethylene occurs with stereospecificity [27][28][29]. The product of acetylene (HC≡CH) reduction in the presence of D 2 O is 96 % cis-ethylene (HDC=CDH), with only 4 % of the trans-isomer [30]. This stereospecificity would be consistent with side-on binding of acetylene to one or more Fe atoms of FeMo-cofactor, with both protons (or deuterons) added to one side of the bound acetylene.…”
Section: Discussionmentioning
confidence: 99%
“…Ed Stiefel suggested a concerted proton and electron addition mechanism to explain this stereospecificity of proton addition to acetylene [31]. Interestingly, it was later found that lowering the electron flux through nitrogenase or substituting certain amino acids around FeMo-cofactor, can relax this stereospecificity, with up to 50 % of the trans-isomer being observed [30,32]. One explanation for this higher level of trans addition of protons is a rearrangement of a semi-reduced intermediate species bound to FeMo-cofactor during catalysis.…”
Section: Discussionmentioning
confidence: 99%